Polycarbonate resin composition and molded article

The polycarbonate resin composition, with a specific blend of copolymers and styrene-acrylonitrile copolymer, addresses the challenges of transparency, color tone, and birefringence, achieving excellent optical performance and stable extrusion productivity.

JP7670597B2Active Publication Date: 2025-04-30MITSUBISHI ENG PLASTICS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021171050
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-10-19
Publication Date
2025-04-30
Estimated Expiration
2041-10-19

AI Technical Summary

Technical Problem

Existing polycarbonate resin compositions face challenges in achieving excellent transparency, color tone, and low birefringence while maintaining stable extrusion productivity, particularly for high-end optical applications.

Method used

A polycarbonate resin composition is developed, containing 15 to 30 parts by mass of a copolymer (B) with styrene, N-phenylmaleimide, and maleic anhydride monomer units, and 8 to 16 parts by mass of a styrene-acrylonitrile copolymer (C) per 100 parts by mass of a polycarbonate resin (A), optimized to achieve compatibility and refractive index adjustment for enhanced transparency and reduced birefringence.

Benefits of technology

The composition achieves excellent transparency with haze of 3% or less, a yellow index of 7 or less, and significantly reduced birefringence, while maintaining stable extrusion productivity, making it suitable for high-end optical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670597000001
    Figure 0007670597000001
  • Figure 0007670597000002
    Figure 0007670597000002
  • Figure 0007670597000003
    Figure 0007670597000003
Patent Text Reader

Abstract

To provide a polycarbonate resin composition that excels in transparency and color tone, has small birefringence, and also has stable extrusion productivity.SOLUTION: A polycarbonate resin composition comprises, relative to 100 pts.mass of a polycarbonate resin (A), 15-30 pts.mass of a copolymer (B) that comprises a styrene monomer unit and an N-phenyl maleimide monomer unit and optionally may comprise a maleic anhydride monomer unit, and 8-16 pts.mass of a styrene-acrylonitrile copolymer (C).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin composition, and more particularly to a polycarbonate resin composition having excellent transparency and color tone and small birefringence, and a molded article thereof. [Background technology]

[0002] Polycarbonate resins are widely used in various fields because they have excellent impact resistance, heat resistance, electrical insulation, dimensional stability, etc., and a good balance of these properties. In particular, polycarbonate resins made from bisphenol compounds have the advantages of being transparent, impact resistance, and heat resistance, and being light and not easily broken, and are therefore used as a substitute for glass in automobile parts, building materials, and optical parts such as lenses. In recent years, they have also been widely used as panel components for display devices used in various mobile terminals such as smartphones, tablet computers, car navigation systems, car audio, portable game consoles, digital cameras, etc., particularly as front components for touch panels, etc.

[0003] When using a resin as an optical member, the optical properties that must be considered are transparency and birefringence. Even if the resin has excellent transparency, it is not preferable for the resin to have a large birefringence. In particular, in cameras, various display devices such as liquid crystal display panels, projectors, etc., if an optical member with a large birefringence is present in the optical path, it will have a negative effect on image quality and signal reading performance, so there is a strong demand for transparent resins with birefringence as small as possible. General polycarbonate resins have large birefringence, and for example, in the case of front components of display devices, if the birefringence is large, uneven phase difference occurs, causing rainbow patterns, and when the screen is viewed through polarized sunglasses, the rainbow patterns become even more severe and cannot be seen, resulting in problems of reduced visibility and significantly reduced design (appearance). General-purpose polycarbonate resins made from bisphenol A have large birefringence, and this problem is prominent.

[0004] Conventionally, various methods have been considered for reducing the birefringence of polycarbonate resins, and it is known to use polycarbonate resins using bisphenols with specific structures, and for example, Patent Document 1 discloses that a special polycarbonate copolymer obtained by copolymerizing spirobisindane bisphenol with bisphenol A has low birefringence. However, such special resins are not general-purpose resins, and therefore require special properties (mechanical properties) and molding conditions, and there are also limitations on their use in terms of cost.

[0005] Patent Document 2 proposes that a resin composition containing styrene-maleic anhydride-N-phenylmaleimide copolymer resin (A) and acrylonitrile-styrene copolymer resin (B) in a ratio of 37-47% resin (A), 13-23% resin (B), and 35-45% polycarbonate resin provides a resin composition with high heat resistance, high transparency, and low birefringence. However, although this composition has a small birefringence, it has insufficient transparency, a large haze value, and a high yellow index (YI), and does not satisfy the high level of transparency and color tone required for high-end optical polycarbonate resin materials in recent years. Furthermore, it has the drawback that the extrusion productivity when pellets are produced from the resin composition is extremely poor. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 06-313035 [Patent Document 2] JP 2013-107933 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and an object (object) of the present invention is to provide a polycarbonate resin composition which is excellent in transparency (haze) and color tone (particularly YI), has small birefringence, and has stable extrusion productivity, and a molded article thereof. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted intensive research to achieve the above object (problem), and as a result have found that the above problem can be solved by a polycarbonate resin composition containing, in a polycarbonate resin, specific amounts of a copolymer (B) which is composed of styrene monomer units and N-phenylmaleimide monomer units and which may have maleic anhydride monomer units, and a styrene-acrylonitrile copolymer (C). The present invention relates to the following polycarbonate resin composition and molded article.

[0009] 1. A polycarbonate resin composition comprising 100 parts by mass of a polycarbonate resin (A), 15 to 30 parts by mass of a copolymer (B) which comprises a styrene monomer unit and an N-phenylmaleimide monomer unit and which may have a maleic anhydride monomer unit, and 8 to 16 parts by mass of a styrene-acrylonitrile copolymer (C). 2. The polycarbonate resin composition according to the above 1, wherein the mass ratio (B) / (C) of the contents of the copolymer (B) and the copolymer (C) is 1.6 to 2.9. 3. A molded article made of the resin composition described in 1 or 2 above. 4. The molded article according to the above item 3, which has a haze of 3% or less when measured in accordance with JIS K7105 when the molded article has a thickness of 2 mm. 5. The molded article according to the above item 3 or 4, which has a yellow index (YI) of 7 or less when measured in accordance with ASTM D1925 when the molded article has a thickness of 2 mm. 6. The molded product according to any one of 3 to 5 above, in which, when the molded product is a plate-shaped molded product having a two-stage shape with dimensions of 90 mm x 50 mm and thicknesses of 3 mm and 2 mm, the average value of the results of area analysis of the retardation over the entire molded product by measurement at three wavelengths of 523 nm, 543 nm and 575 nm using a wide-range two-dimensional birefringence evaluation system manufactured by Photonic Lattice is 200 nm or less. 7. The molded article according to any one of the above items 3 to 6, which is an optical molded article. Effect of the Invention

[0010] The polycarbonate resin composition of the present invention has excellent transparency and color tone, small birefringence, and stable extrusion productivity. In order to reduce the birefringence of general-purpose polycarbonate resin, alloying with a material having the opposite negative birefringence to polycarbonate resin reduces the phase difference, but adding a general styrene-based resin causes cloudiness due to the difference in refractive index. The copolymer (C) used in the present invention has negative birefringence and a refractive index lower than that of polycarbonate resin (A), and copolymer (B) has a higher refractive index than polycarbonate resin (A) and has negative birefringence, but by blending both (B) and (C) in the above-mentioned amounts, (B) and (C), which are compatible with each other, become islands with a refractive index equivalent to that of polycarbonate resin (A) in the matrix (sea) of polycarbonate resin (A), resulting in excellent transparency, and by fully offsetting the positive birefringence of polycarbonate resin (A), both transparency and low birefringence can be achieved at the same time, and the color tone is also excellent, allowing stable extrusion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Each component constituting the polycarbonate resin composition of the present invention will be described in detail below. In this specification, when a range is expressed using "to" with numerical values ​​or physical property values ​​on either side, this means a range that includes the values ​​before and after the range.

[0012] The polycarbonate resin composition of the present invention is characterized by containing, per 100 parts by mass of a polycarbonate resin (A), 15 to 30 parts by mass of a copolymer (B) which is composed of styrene monomer units and N-phenylmaleimide monomer units and may have maleic anhydride monomer units, and 8 to 16 parts by mass of a styrene-acrylonitrile copolymer (C).

[0013] [Polycarbonate resin (A)] As the polycarbonate resin (A), an aromatic polycarbonate resin having an aromatic ring in the main chain is preferred because of its large effect of reducing birefringence.

[0014] The aromatic polycarbonate resin is an aromatic polycarbonate polymer obtained by reacting an aromatic hydroxy compound with phosgene or a diester of carbonic acid. The aromatic polycarbonate polymer may have a branch. The method for producing the aromatic polycarbonate resin is not particularly limited, and may be a conventional method such as the phosgene method (interfacial polymerization method) or the melting method (ester exchange method).

[0015] Representative examples of aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane (i.e., bisphenol C), 2,2-bis(4-hydroxy-3-t-butylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 4,4-bis(4-hydroxyphenyl)heptane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 4,4'-dihydroxybiphenyl, 3,3',5,5'-tetramethyl-4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ether, and bis(4-hydroxyphenyl)ketone.

[0016] Suitable aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane (i.e., bisphenol C), and the like. In particular, in the resin composition of the present invention, the effect of reducing birefringence achieved by combining the copolymer (B) and the copolymer (C) in the specific composition ratio is large, and also from the viewpoint of the economy of using a general-purpose resin, a polycarbonate resin derived from bisphenol A is particularly preferred. It is also preferable to blend a polycarbonate resin derived from bisphenol C with a polycarbonate resin derived from bisphenol A, but in this case, the amount of the polycarbonate resin derived from bisphenol C is preferably 10% by mass or less from the viewpoint of adjusting the birefringence. In addition, a copolymerized polycarbonate resin of bisphenol A and bisphenol C may be used, but in this case, the amount of copolymerization is also preferably 10% by mass or less.

[0017] When producing an aromatic polycarbonate resin, a small amount of a polyhydric phenol having three or more hydroxy groups in the molecule may be added in addition to the above aromatic dihydroxy compound. In this case, the aromatic polycarbonate resin will have branches. Examples of the polyhydric phenol having three or more hydroxyl groups include polyhydroxy compounds such as phloroglucin, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 2,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-3, 1,3,5-tris(4-hydroxyphenyl)benzene, and 1,1,1-tris(4-hydroxyphenyl)ethane, or 3,3-bis(4-hydroxyaryl)oxindole (i.e., isatin bisphenol), 5-chloruisatin, 5,7-dichloruisatin, and 5-bromoisatin. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane or 1,3,5-tris(4-hydroxyphenyl)benzene is preferred. The amount of the polyhydric phenol used is preferably 0.01 to 10 mol %, and more preferably 0.1 to 2 mol %, based on the amount of the aromatic dihydroxy compound (100 mol %).

[0018] In the polymerization by the transesterification method, a carbonic acid diester is used as a monomer instead of phosgene. Representative examples of the carbonic acid diester include diphenyl carbonate, substituted diaryl carbonates such as ditolyl carbonate, and dialkyl carbonates such as dimethyl carbonate, diethyl carbonate, and di-tert-butyl carbonate. These carbonic acid diesters can be used alone or in combination of two or more. Among these, diphenyl carbonate and substituted diphenyl carbonate are preferred.

[0019] In order to improve the appearance and flowability of the molded article, the polycarbonate resin (A) may contain a polycarbonate oligomer. The viscosity average molecular weight [Mv] of this polycarbonate oligomer is usually 1500 or more, preferably 2000 or more, and usually 9500 or less, preferably 9000 or less. Furthermore, the amount of the polycarbonate oligomer contained is preferably 30% by mass or less of the polycarbonate resin (A) (including the polycarbonate oligomer).

[0020] Furthermore, the polycarbonate resin may be not only a virgin raw material, but also a polycarbonate resin regenerated from a used product (so-called material-recycled polycarbonate resin). However, the recycled polycarbonate resin is preferably 80% by mass or less of the polycarbonate resin (A), more preferably 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less. Since the recycled polycarbonate resin may be deteriorated by heat degradation or aging, if such a polycarbonate resin is used in an amount greater than the above range, the hue and mechanical properties may be deteriorated.

[0021] The refractive index of the polycarbonate resin (A) is preferably intermediate between those of the copolymer (B) and the copolymer (C), and is preferably about 1.575 to 1.585. The polycarbonate resin (A) may be a mixture of two or more polycarbonate resins having different refractive indices. In this case, a polycarbonate resin having a refractive index outside the above preferred range may be mixed to adjust the refractive index within the above range.

[0022] In the present invention, the refractive indexes of the polycarbonate resin (A), the copolymer (B) and the copolymer (C) are values ​​measured in accordance with JIS K7142 at a temperature of 23±1°C, a humidity of 50±5% RH and a sodium D line at 589 nm.

[0023] The viscosity average molecular weight Mv of the polycarbonate resin (A) is preferably in the range of 10,000 to 50,000, more preferably not more than 45,000, further preferably not more than 40,000, and particularly preferably not more than 38,000. In the case of an optical molded article, it is preferably 10,000 to 30,000, and a viscosity average molecular weight in this range provides excellent fluidity (moldability), hue, and mechanical strength, making it suitable for an optical molded article. Two or more kinds of polycarbonate resins having different viscosity average molecular weights may be mixed and used. In this case, polycarbonate resins having a viscosity average molecular weight outside the above-mentioned preferable range may be mixed.

[0024] The viscosity average molecular weight Mv of the polycarbonate resin (A) was calculated by measuring the intrinsic viscosity [η] (unit: dl / g) at 25°C using a Ubbelohde viscometer with methylene chloride as a solvent, and then calculating the viscosity average molecular weight Mv using the Schnell viscosity formula, η = 1.23 × 10 -4 Mv 0.83 The intrinsic viscosity [η] is the value calculated from the specific viscosity [η sp ] was measured and the value was calculated according to the following formula.

number

[0025] [Copolymer (B)] The polycarbonate resin composition of the present invention contains a copolymer (B) which is composed of styrene monomer units and N-phenylmaleimide monomer units and which may have maleic anhydride monomer units.

[0026] The copolymer (B) is preferably a copolymer consisting of 40 to 60% by mass of styrene monomer units, 40 to 55% by mass of N-phenylmaleimide monomer units, and 0 to 10% by mass of maleic anhydride monomer units (based on a total of 100% by mass of these units). If the styrene monomer units are less than 40% by mass, the strength and refractive index of the composition tend to be low, and if they exceed 60% by mass, the heat resistance of the composition tends to decrease. If the maleic anhydride monomer units exceed 10% by mass, the thermal stability tends to deteriorate, and poor color tone and appearance tend to occur. If the N-phenylmaleimide monomer units exceed 55% by mass, the strength of the composition tends to be extremely low. More preferred proportions of each unit, based on 100% by mass of the total of each unit, are styrene monomer unit: 47 to 51% by mass, N-phenylmaleimide monomer unit: 42 to 52% by mass, and maleic anhydride monomer unit: 1 to 7% by mass.

[0027] The copolymer (B) can be produced by a known method, for example, a method of copolymerizing a monomer mixture consisting of a styrene monomer, an N-phenylmaleimide monomer, a maleic anhydride monomer, and other copolymerizable monomers, or a method of copolymerizing a monomer mixture consisting of a styrene monomer, a maleic anhydride monomer, and other copolymerizable monomers, and then reacting a part or all of the maleic anhydride monomer units with aniline to imidize them and convert them into N-phenylmaleimide monomers.

[0028] As described above, the refractive index of the polycarbonate resin (A) is preferably in the range of 1.575 to 1.585, and the copolymer (B) preferably has a higher refractive index. The refractive index of the copolymer (B), where nA is the refractive index of the polycarbonate resin (A) and nB is the refractive index of the copolymer (B), is preferably nB-nA, which is greater than 0 and is 0.05 or less, more preferably 0.04 or less, and even more preferably 0.03 or less. This can further improve the transparency of the resin composition.

[0029] The content of the copolymer (B) is 15 to 30 parts by mass relative to 100 parts by mass of the polycarbonate resin (A). By including the styrene-acrylonitrile copolymer (C) in such a range, the transparency and low birefringence of the resin composition can be achieved, the resin composition does not become yellowish, and the difficulty of kneading during extrusion production of the resin composition can be resolved. The content of the copolymer (B) is preferably 16 parts by mass or more, and preferably 28 parts by mass or less, more preferably 27 parts by mass or less, and particularly preferably 26 parts by mass or less.

[0030] [Styrene-acrylonitrile copolymer (C)] The polycarbonate resin composition of the present invention contains a styrene-acrylonitrile copolymer (C). The styrene-acrylonitrile copolymer (C) is a copolymer of acrylonitrile and styrene.

[0031] Examples of the styrene-based monomer constituting the styrene-acrylonitrile copolymer (C) include styrene, α-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, with styrene and α-methylstyrene being more preferred, and styrene being particularly preferred.

[0032] The styrene-acrylonitrile copolymer (C) may be a copolymer of acrylonitrile and a copolymerizable monomer other than styrene. Examples of the copolymerizable monomer other than styrene and acrylonitrile include α-methylstyrene, (meth)acrylic acid ester monomers, and α,β-unsaturated carboxylic acids and their anhydrides, such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, phthalic acid, and itaconic acid.

[0033] The refractive index of the styrene-acrylonitrile copolymer (C), where nA is the refractive index of the polycarbonate resin (A) and nC is the refractive index of the styrene-acrylonitrile copolymer (C), is preferably such that nA-nC is greater than 0 and is 0.05 or less, more preferably 0.04 or less, and even more preferably 0.03 or less.

[0034] The amount of styrene-derived units in the styrene-acrylonitrile copolymer (C) is preferably 65% ​​by mass or more, more preferably 70% by mass or more, and preferably 85% by mass or less, particularly preferably 80% by mass or less, and particularly preferably 75% by mass or less, based on the total amount of 100% by mass. The preferred amount of acrylonitrile is the amount obtained by subtracting these amounts from 100% by mass. By setting the amount of styrene units in the copolymer (C) in this way, it is possible to achieve higher transparency and lower birefringence value (retardation) of the resin composition.

[0035] When the styrene-acrylonitrile copolymer (C) is a copolymer of acrylonitrile and a copolymerizable monomer other than styrene, the amount of units derived from the other copolymerizable monomer is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 10 mass% or less, among which 5 mass% or less, 3 mass% or less, 2 mass% or less, and particularly preferably 1 mass% or less, in 100 mass% of the copolymer (C).

[0036] The styrene-acrylonitrile copolymer (C) is preferably an acrylonitrile-styrene resin consisting of acrylonitrile and styrene, which is usually called AS resin.

[0037] The method for producing the styrene-acrylonitrile copolymer (C) is not limited, and any known method can be used, such as bulk polymerization, emulsion polymerization, solution polymerization, and suspension polymerization.

[0038] The content of the styrene-acrylonitrile copolymer (C) is 8 to 16 parts by mass relative to 100 parts by mass of the polycarbonate resin (A). By including the copolymer (B) in such a range, the copolymer (C) is completely compatible with the copolymer (B), making it easy to adjust the refractive index, and it is possible to achieve a high level of transparency (haze), color tone, and low birefringence, thereby improving extrusion productivity during the production of the resin composition. If the content of the styrene-acrylonitrile copolymer (C) is less than 8 parts by mass, the birefringence improvement effect is low even if an optimal amount of the copolymer (B) is blended, and if it exceeds 16 parts by mass, the extrudability deteriorates, the color tone and haze also deteriorate, and the heat resistance is likely to decrease. The content of the copolymer (C) is preferably 8.5 parts by mass or more, and preferably 15 parts by mass or less, and more preferably 14 parts by mass or less.

[0039] The total content of copolymer (B) and copolymer (C) is preferably 23 to 46 parts by mass, more preferably 24 parts by mass or more, more preferably 25 parts by mass or more, and more preferably 44 parts by mass or less, and more preferably 42 parts by mass or less, more preferably 40 parts by mass or less, per 100 parts by mass of polycarbonate resin (A).

[0040] The mass ratio (B) / (C) of the content of copolymer (B) and copolymer (C) is preferably 1.6 to 2.9. By being in such a range, the refractive index of the polycarbonate resin (A) portion and the refractive index of the copolymer (B) and copolymer (C) portions become close to each other, so that the transparency becomes closer and the haze value also decreases, which is preferable. (B) / (C) is more preferably 1.75 or more, even more preferably 1.83 or more, more preferably 2 or less, and even more preferably 1.9 or less.

[0041] [Stabilizer] The polycarbonate resin composition of the present invention preferably contains a stabilizer, and the stabilizer is preferably a phosphorus-based stabilizer or a phenol-based stabilizer.

[0042] Any known phosphorus stabilizer can be used as the phosphorus stabilizer. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds and organic phosphate compounds being particularly preferred.

[0043] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite.

[0044] As the organic phosphate compound, organic phosphate metal salts can be suitably used, specifically, a mixture of zinc salt of distearyl acid phosphate and zinc salt of monostearyl acid phosphate, mono- and di-stearyl acid phosphate, etc. can be mentioned.

[0045] The phosphorus-based stabilizer may be contained alone or in any combination and ratio of two or more kinds.

[0046] The content of the phosphorus-based stabilizer is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and usually 1 part by mass or less, preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). If the content of the phosphorus-based stabilizer is less than the lower limit of the above range, the thermal stabilization effect may be insufficient, and if the content of the phosphorus-based stabilizer is more than the upper limit of the above range, the effect may plateau and become uneconomical.

[0047] The phenol-based stabilizer includes, for example, a hindered phenol-based antioxidant. Specific examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6- triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0048] Among these, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. The phenol-based stabilizer may be contained alone or in any combination and ratio of two or more kinds.

[0049] The content of the phenolic stabilizer is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). If the content of the phenolic stabilizer is less than the lower limit of the above range, the effect of the phenolic stabilizer may be insufficient, and if the content of the phenolic stabilizer is more than the upper limit of the above range, the effect may plateau and become uneconomical.

[0050] [Release agent] The polycarbonate resin composition of the present invention preferably contains a mold release agent. As the mold release agent, known mold release agents usually used for resins can be used, but polyolefin compounds and fatty acid ester compounds are preferred.

[0051] The polyolefin-based compound may be a compound selected from paraffin wax and polyethylene wax, and among them, those having a weight average molecular weight of 700 to 10,000, more preferably 900 to 8,000, are preferred.

[0052] Examples of fatty acid ester compounds include fatty acid esters such as saturated or unsaturated monovalent or divalent aliphatic carboxylic acid esters, glycerin fatty acid esters, sorbitan fatty acid esters, and partially saponified products thereof, etc. Among these, mono- or di-fatty acid esters composed of a fatty acid having 11 to 28 carbon atoms, preferably 17 to 21 carbon atoms, and an alcohol are preferred.

[0053] Examples of fatty acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, azelaic acid, etc. The fatty acid may also be alicyclic. Examples of the alcohol include saturated or unsaturated monohydric or polyhydric alcohols. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, monohydric or polyhydric saturated alcohols having 30 or less carbon atoms are preferred, and aliphatic saturated monohydric or polyhydric alcohols having 30 or less carbon atoms are more preferred. Here, the term "aliphatic" also includes alicyclic compounds. Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol. The above ester compound may contain an aliphatic carboxylic acid and / or an alcohol as an impurity, and may be a mixture of a plurality of compounds.

[0054] Specific examples of fatty acid ester compounds include glycerin monostearate, glycerin monobehenate, glycerin dibehenate, glycerin-12-hydroxymonostearate, sorbitan monobehenate, pentaerythritol monostearate, pentaerythritol distearate, stearyl stearate, and ethylene glycol montanic acid ester.

[0055] The content of the release agent is preferably 0.1 to 3 parts by mass, more preferably 0.2 to 2.5 parts by mass, and even more preferably 0.25 to 2 parts by mass, based on 100 parts by mass of the polycarbonate resin (A). If it is less than 0.1 part by mass, the surface properties tend to deteriorate due to poor release during melt molding, while if it exceeds 3 parts by mass, the workability of kneading the resin composition tends to deteriorate and the surface of the molded product tends to become cloudy.

[0056] [Additives, etc.] The resin composition may contain additives other than those described above, such as ultraviolet absorbers, antistatic agents, antibacterial agents, flame retardants, flame retardant assistants (anti-dripping agents), fluorescent brighteners, plasticizers, compatibilizers, etc., to the extent that transparency is not impaired. These additives may be blended alone or in combination of two or more.

[0057] [Production of resin composition] There is no limitation on the method for producing the polycarbonate resin composition of the present invention, and a wide variety of known methods for producing polycarbonate resin compositions can be used. Examples of such methods include a method in which the polycarbonate resin (A), the copolymer (B) and the copolymer (C), and other components to be blended as necessary are premixed using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader.

[0058] The polycarbonate resin composition of the present invention can be pelletized to produce various molded articles by various molding methods. Alternatively, the resin can be melt-kneaded in an extruder and directly molded into a molded article without going through the pelletizing process.

[0059] The polycarbonate resin composition of the present invention has excellent transparency, and its haze, measured in accordance with JIS K7105 on a 2 mm-thick molded article molded from the resin composition, is preferably 3% or less. The specific method for measuring the haze value is as described in the Examples.

[0060] The polycarbonate resin composition of the present invention has excellent color tone, and its YI, measured in accordance with ASTM D1925 for a 2 mm-thick molded article molded from the resin composition, is preferably 7 or less, and more preferably 6.5 or less. The specific method for measuring YI is as described in the Examples.

[0061] The polycarbonate resin composition of the present invention is characterized by its small birefringence. A two-stage plate-shaped molded article having dimensions of 90 mm x 50 mm and thicknesses of 3 mm and 2 mm, which is molded from the resin composition, is subjected to area analysis of the phase difference over the entire plate-shaped molded article by measurement at three wavelengths, 523 nm, 543 nm, and 575 nm, using a wide-range two-dimensional birefringence evaluation system manufactured by Photonic Lattice, Inc. The average value of the results is preferably 200 nm or less, more preferably 190 nm or less. The specific method for measuring the phase difference is as described in the Examples.

[0062] The polycarbonate resin composition of the present invention has excellent transparency and color tone, and has extremely reduced birefringence.Therefore, its applications include optical molded articles, specifically, various lenses, such as lenses for various cameras, telescopes, microscopes, projectors, optical measuring devices, etc., various optical disks, home televisions, personal computer displays, car navigation systems, car audio, and other in-vehicle display devices, smartphones, head-mounted displays, barcode readers, scanners, and other display device panel members and films.In particular, it can be suitably used as panel members for display devices used in various mobile terminals such as smartphones, tablet-type personal computers, car navigation systems, car audio, portable game consoles, digital cameras, etc., particularly as front members for display devices. EXAMPLES

[0063] The present invention will be described in more detail below with reference to examples, although the present invention should not be construed as being limited to the following examples.

[0064] The raw materials used in the following Examples and Comparative Examples are as shown in Table 1 below. [Table 1]

[0065] (Examples 1 to 5, Comparative Examples 1 to 7) [Production of resin composition pellets] The raw materials shown in Table 1 were blended in the ratios (parts by mass) shown in Table 2 and mixed in a tumbler for 20 minutes. The mixture was then melt-kneaded using a twin-screw extruder ("TEM-26SX" manufactured by Shibaura Machine Co., Ltd.) at a cylinder temperature of 260°C and a discharge rate of 25 kg / h, and pellets of a polycarbonate resin composition were obtained by strand cutting. The obtained pellets were dried in a hot air circulation dryer at 120°C for 5 hours, and then an injection molding machine ("J55AD-60H" manufactured by The Japan Steel Works, Ltd.) was used to obtain two-tiered plate-shaped test pieces with long sides of 90 mm, short sides of 50 mm, and two-tiered shapes with thicknesses of 2 mm and 3 mm separated by the center of the long sides, at a cylinder temperature of 280°C and a mold temperature of 80°C. The obtained test pieces were subjected to the following evaluations, and the results are shown in Table 2.

[0066] [Haze (unit: %)] The haze (unit: %) of the 2 mm thick portion of the two-stage plate-shaped test piece obtained above was measured using a haze meter ("SE6000" manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7105. [Yellow Index (YI)] The yellow index (YI) of the 2 mm thick portion of the two-stage plate-shaped test piece obtained above was measured using a color difference meter ("SE6000" manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with ASTM D1925.

[0067] [Average retardation of molded product] A wide-range two-dimensional birefringence evaluation device (Photonic Lattice's "WPA-200-L") was used to perform area analysis of the phase difference over the entire two-stage plate-shaped specimen obtained above using three wavelength measurements (wavelengths of 523 nm, 543 nm, and 575 nm), and the average value (average retardation, unit: nm) was calculated.

[0068] [Evaluation of extrusion productivity] The extrusion productivity (easy productivity) when pellets were produced by the above method was evaluated according to the following criteria. ◎: Strands can be pulled easily ○: Strands can be pulled △: Strand breakage occurs ×: Strand breakage occurs frequently The above evaluation results are shown in Table 2 below.

[0069] [Table 2] [Industrial Applicability]

[0070] The polycarbonate resin composition of the present invention is a high-performance polycarbonate resin material which achieves a good balance between transparency, color tone, and low birefringence and is also reasonably priced, and therefore can be suitably used particularly for various optical molded articles.

Claims

1. A polycarbonate resin composition comprising, per 100 parts by mass of a polycarbonate resin (A), 15 to 25 parts by mass of a copolymer (B) which is composed of a styrene monomer unit and an N-phenylmaleimide monomer unit and which may have a maleic anhydride monomer unit, and 8 to 16 parts by mass of a styrene-acrylonitrile copolymer (C), and wherein the mass ratio (B) / (C) of the contents of the copolymer (B) to the copolymer (C) is 1.6 to 2.

9.

2. A molded article made of the resin composition according to claim 1.

3. 3. The molded article according to claim 2, which has a haze of 3% or less when measured in accordance with JIS K7105 when the molded article has a thickness of 2 mm.

4. 4. The molded article according to claim 2 or 3, which has a yellow index (YI) of 7 or less when measured in accordance with ASTM D1925 when the molded article has a thickness of 2 mm.

5. When the molded product is a plate-shaped molded product having a two-stage shape of 90 mm x 50 mm and a thickness of 3 mm and 2 mm, the average value of the results of area analysis of the phase difference in the entire molded product by measuring at three wavelengths of 523 nm, 543 nm and 575 nm using a wide-range two-dimensional birefringence evaluation system manufactured by Photonic Lattice is 200 nm or less.

6. The molded article according to any one of claims 2 to 5, which is an optical molded article.

Citation Information

Patent Citations

  • Polycarbonate copolymer from spirobisindan and bisphenol a, its production, and optical member made of it

    JP1994313035A

  • Resin composition for optical molded article, method for producing the same and optical molded article

    JP2013107933A

  • Resin composition, molding, housing for household electrical appliance and inner layer member for vehicle

    JP2014047346A